Hydrolysis of bile acid conjugates and dehydroxylation of cholic acid by Clostridium bifermentans : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biotechnology - Archer, Richard Hamilton (Massey University, 1980)
The transformation of bile acids by Clostridium bifermentans was studied with a view to developing a process whereby the bile acid conjugates of New Zealand mutton and beef gall may be converted to deoxycholic acid. Statistically designed experiments were employed to maximise 7α-dehydroxylation of cholic acid to deoxycholic acid and to minimise the 7α-dehydrogenation of cholic acid to 7-ketodeoxycholic acid. Both transformations showed optima near pH 7. High deoxycholate yields were associated with conditions less favourable to strong growth and with relatively high electrode potentials. 7-ketodeoxycholic acid production was not as sensitive to environmental factors as was 7α-de-hydroxylation and could not be eliminated merely by manipulating fermentation variables. Studies on the 7α-dehydrogenation of cholic acid with washed resting-stage cells of Cl. bifermentans indicated several means of manipulating 7-ketodeoxycholate yields which were then tested using batch fermentation. In the presence of Zn++ions, 7-ketodeoxycholate yields were reduced but dehydroxylation was completely inhibited. In the presence of EDTA, 7α-dehydrogenation was almost quantitative but deoxycholate yields were again nil. Both transformations were enhanced during aerobic incubation. The highest deoxycholate yield observed during the work (50 molar %) was obtained by sweeping the fermenter headspace with air. Growing cells of Cl. bifermentans effected the near-quantitative hydrolysis of glycodeoxycholate, taurodeoxycholate and taurocholate within 48 h whilst glycocholate was 90% deconjugated. At substrate concentrations greater than 0.1% w/v however, taurine conjugates were less well hydrolysed.
Keywords: Clostridium bifermentans; Bile acid; Cholic acid